Application of a Surface Waveguide in Microwave Drying Units of the Agribusiness Industry - Ekaterina Ritter; Alexey Savostin; Dmitry Ritter; Galina Savostina; Andrey Smirnov; Sayat Moldakhmetov (International Journal of Agronomy)
In the last two decades, the electromagnetic field of the microwave range has been successfully introduced into various branches of the agribusiness industry as one of the most promising and advanced technologies for drying manufactured products. In this regard, the article proposes a new microwave irradiation technique for drying various objects based on a surface waveguide’s properties. The paper analyses the main links that make up the surface waveguide as a microwave irradiation system and shows the ways of their implementation. The article describes the advantages of applying a vibratory device for exciting a surface wave, using a re-emitting antenna array, and operating a single conductor with a dielectric coating as a surface waveguide. Such advantages make it possible to introduce microwave drying units with the required distribution of electromagnetic field energy along the irradiated material, small dimensions, high drying quality, and low price.